Examining Work-Life Balance among Women Entrepreneurs in the Private Sector: A Comparative Analysis of Single and Married Individuals. - Kitsirapakin, Preeyanan; Juajamsai, Kanjana; Houng-ngam, Jongrak (MBA-KKU Journal, 2024)
Although we understand that in most leadership positions, males outnumber females significantly, the minority of women who have advanced to the highest echelons of leadership in organizations or businesses often possess characteristics distinct from most women. Additionally, being a woman necessitates roles as a wife and mother, involving household responsibilities. What is intriguing is whether single female leaders manage their lives differently from married ones. This study utilized a qualitative research approach wherein semi-structured interviews were conducted with ten female entrepreneurs from the Northeast region of Thailand, including five single and five married individuals. The interviews explored their understanding of work-life balance, the hurdles they encountered, the significance of family support, stress management strategies, and their perspectives on achieving work-life balance. The findings reveal that both single and married female entrepreneurs have a similar comprehension of work-life balance, recognizing the need to allocate time to their work and personal lives. Nonetheless, both groups face challenges arising from external factors and time constraints. Intriguingly, the study unveils contrasting family support expectations, with single entrepreneurs seeking financial assistance from their families and married entrepreneurs valuing emotional encouragement. Regarding stress management, singles tend to seek solace in activities with friends, whilst married individuals prefer to prioritize quality time with their families.